VITAMIN B SUPPLEMENTATION IN GERIATRIC PATIENTS: A POTENTIAL STRATEGY TO MANAGING HYPERHOMOCYSTEINEMIA IN CEREBROVASCULAR DISEASE - Meryana, Meryana,; Sugianto, Paulus; Erwin, Ferdinand; Jaya, David Karunia (JURNAL WIDYA MEDIKA, 2024)
Homocysteine is a non-essential amino acid produced in the biosynthesis pathway between methionine and cysteine. Its levels tend to rise with age due to physiological, lifestyle, and nutritional factors. Elevated homocysteine can induce oxidative stress, inflammation, and endothelial dysfunction, which are critical in the development of cerebrovascular diseases. These mechanisms involve increased free radicals, decreased antioxidant enzyme activity, and enhanced inflammatory responses. Specifically, elevated homocysteine heightens oxidative stress and inflammation by increasing pro-inflammatory cytokines and decreasing anti-inflammatory cytokines, leading to endothelial cell damage and apoptosis. Supplementation with vitamins B6, B9, and B12 has been shown to lower homocysteine levels and reduce the risk of ischemic stroke. However, there is currently no established guideline for the appropriate dosing of these vitamins.